(untitled) (Journal of Economic Research & Business Administration, 2015)
"This article is about problems of increase of efficiency of use of logistics at the enterprises are considered. The author makes the short analysis of logistical expenses, influence of system ""KANBAN"" on the organization of works of the various enterprises also is considered. "